2003
DOI: 10.1002/cncr.11193
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight inhibitors of matrix metalloproteinases can enhance the expression of matrix metalloproteinase‐2 (gelatinase A) without inhibiting its activation

Abstract: BACKGROUNDIn the current study, the authors investigated the effects of synthetic low molecular weight inhibitors of matrix metalloproteinases (MMPs) on the expression and activation of MMP‐2 in a three‐dimensional tissue system.METHODSRabbit periosteal explants were cultured with or without various concentrations of the MMP inhibitors CT1166, CT1399, or CT1746, and conditioned media and tissue extracts were analyzed for the expression and activity of MMP‐2.RESULTSThe data showed that blocking the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In a previous study, we found an up‐regulation of MMP‐2 protein expression by several CMTs, including CMT‐3, in two‐dimensional cultures (18). An up‐regulation of MMP‐2 was also shown for periosteal cells incubated with other synthetic inhibitors (49). These data indicate that MMP inhibitors might have unexpected stimulatory effects on MMP production via positive feedback mechanisms.…”
Section: Discussionmentioning
confidence: 75%
“…In a previous study, we found an up‐regulation of MMP‐2 protein expression by several CMTs, including CMT‐3, in two‐dimensional cultures (18). An up‐regulation of MMP‐2 was also shown for periosteal cells incubated with other synthetic inhibitors (49). These data indicate that MMP inhibitors might have unexpected stimulatory effects on MMP production via positive feedback mechanisms.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, seizure‐mediated increases of gelatinase expression and activity in the WT, but not in the mutant mice, suggest paradoxically that TIMP‐1 increases gelatinase expression and/or activity in the brain. Analogous effects of TIMPs or MMPIs have been described in other tissues: TIMP‐1 induces gelatinase expression in hepatocytes (Roeb et al ., 1999); TIMP‐2 is involved in MMP‐2 activation by MT1‐MMP, both in vitro (Murphy et al ., 2003) and in vivo (Wang et al ., 2000), and synthetic MMPIs can enhance MMP‐2 expression without inhibiting its activation (Kerkvliet et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study (27), on the other hand, described an inhibitory effect on MMP‐2 and ‐9 protein expression by porcine PDL epithelial cells at similar concentrations. Moreover, other synthetic MMP inhibitors have been shown to increase MMP‐2 mRNA and protein expression at low concentrations in rabbit periosteal cell cultures (42). The increase in MMP‐2 expression by PDL cells, as shown in our study, has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%